Buparlisib plus fulvestrant in postmenopausal women with hormone-receptor-positive, HER2-negative, advanced breast cancer progressing on or after mTOR inhibition (BELLE-3): a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 1 (January 2018) - Di Leo, Angelo; Johnston, Stephen; Lee, Keun Seok; Ciruelos, Eva; Lønning, Per E; Janni, Wolfgang; O'Regan, Ruth; Mouret-Reynier, Marie-Ange; Kalev, Dimitar; Egle, Daniel; Csőszi, Tibor; Bordonaro, Roberto; et al.
Summary: Background: Activation of the PI3K/AKT/mTOR pathway occurs frequently in breast cancer that is resistant to endocrine therapy. Approved mTOR inhibitors effectively inhibit cell growth and proliferation but elicit AKT phosphorylation via a feedback activation pathway, potentially leading to resistance to mTOR inhibitors. We evaluated the efficacy and safety of buparlisib plus fulvestrant in patients with advanced breast cancer who were pretreated with endocrine therapy and mTOR inhibitors. Methods: BELLE-3 was a randomised, double-blind, placebo-controlled, multicentre, phase 3 study. Postmenopausal women aged 18 years or older with histologically or cytologically confirmed hormone-receptor-positive, HER2-negative, locally advanced or metastatic breast cancer, who had relapsed on or after endocrine therapy and mTOR inhibitors, were recruited from 200 trial centres in 22 countries. Eligible patients were randomly assigned (2:1) via interactive response technology (block size of six) to receive oral buparlisib (100 mg per day) or matching placebo starting on day 1 of cycle 1, plus intramuscular fulvestrant (500 mg) on days 1 and 15 of cycle 1 and on day 1 of subsequent 28-day cycles. Randomisation was stratified by visceral disease status. The primary endpoint was progression-free survival by local investigator assessment as per the Response Evaluation Criteria In Solid Tumors (RECIST) version 1.1 in the full analysis population (all randomised patients, by intention-to-treat). Safety was analysed in all patients who received at least one dose of treatment and at least one post-baseline safety assessment. This study is registered with ClinicalTrials.gov, number NCT01633060, and is ongoing but no longer enrolling patients. Findings: Between Jan 15, 2013, and March 31, 2016, 432 patients were randomly assigned to the buparlisib (n=289) or placebo (n=143) groups. Median progression-free survival was significantly longer in the buparlisib versus placebo group (3·9 months [95% CI 2·8–4·2] vs 1·8 months [1·5–2·8]; hazard ratio [HR] 0·67, 95% CI 0·53–0·84, one-sided p=0·00030). The most frequent grade 3–4 adverse events in the buparlisib versus placebo group were elevated alanine aminotransferase (63 [22%] of 288 patients vs four [3%] of 140), elevated aspartate aminotransferase (51 [18%] vs four [3%]), hyperglycaemia (35 [12%] vs none), hypertension (16 [6%] vs six [4%]), and fatigue (ten [3%] vs two [1%]). Serious adverse events were reported in 64 (22%) of 288 patients in the buparlisib group versus 23 (16%) of 140 in the placebo group; the most frequent serious adverse events (affecting ≥2% of patients) were elevated aspartate aminotransferase (six [2%] vs none), dyspnoea (six [2%] vs one [1%]), and pleural effusion (six [2%] vs none). On-treatment deaths occurred in ten (3%) of 288 patients in the buparlisib group and in six (4%) of 140 in the placebo group; most deaths were due to metastatic breast cancer, and two were considered treatment-related (cardiac failure [n=1] in the buparlisib group and unknown reason [n=1] in the placebo group). Interpretation: The safety profile of buparlisib plus fulvestrant does not support its further development in this setting. Nonetheless, the efficacy of buparlisib supports the rationale for the use of PI3K inhibitors plus endocrine therapy in patients with PIK3CA mutations. Funding: Novartis Pharmaceuticals Corporation.